Hyperaccumulator plant discoveries in the Balkans: accumulation, distribution, and practical applications - Ksenija Jakovljević; Aida Bani; Dolja Pavlova; Maria Konstantinou; Panayiotis G. DimitrakopoulosPanayiotis G. Dimitrakopoulos; Dimitris Kyrkas; Roger D. Reeves; Tomica Mišljenović; Gordana Tomović; Antony van der Ent; Alan J.M. Baker; Katerina Bačeva Andonovska; et al. (Botanica Serbica, 2022)
Hyperaccumulator plants are able to tolerate extremely high concentrations of metals/metalloids in the soil in which they grow and to accumulate high concentrations in their shoots. To date, a total of 31 hyperaccumulator plant species have been identified in the Balkans, the centre of diversity and speciation in the European flora which is particularly rich in ultramafic areas. A further 8 species have yet to be confirmed through additional studies. Most of the 31 hyperaccumulator taxa (13 taxa or 41.9%) are species of the genus Odontarrhena, all hyperaccumulating Ni, but concentrations of this element above the hyperaccumulation threshold were also found in the genera Bornmuellera and Noccaea (all Brassicaceae), Orobanche (Orobanchaceae), Centaurea (Asteraceae) and Viola (Violaceae). The existence of hyperaccumulators of Tl and Zn is of particular interest because very few species worldwide hyperaccumulate these elements. Multiple metal hyperaccumulation was found in Noccaea kovatsii, as the hyperaccumulation of Zn was found in this species in addition to Ni, the primary accumulated element. Metal hyperaccumulation is discussed in terms of phylogenetic relationships and species distributions, with special attention to their systematics, the detection and recognition of new hyperaccumulating species and the possibilities for their future practical applications in phytotechnologies.